Producing cultural space in the Chinese cities: a case study of grand theaters in Shanghai - Xue, Charlie Qiuli; Sun, Cong; Zhang, Lujia (Journal of Architecture and Urbanism, 2020)
Following the rapid pace of urbanisation, Chinese cities have launched a new wave of large-scale infrastructure, including cultural building construction. From 1998 to 2015, more than 360 grand theaters were built together with libraries, museums and children’s palaces. The number of newly built theaters may have been more than the total sum built in Europe over the past 70 years. Through case studies of theaters built in Shanghai, this paper penetrates the phenomenon of the “heat of cultural buildings” and discovers the history, intentions and effects of these theaters on Chinese cities. Following on-site investigation of the city and theaters, the materials of theater building in China are presented. Theaters of various types are discussed in the framework of urban space, design language and consumerist culture. The authors find that the rapid growth of cultural facilities epitomises the ambition and strong implementation of Chinese (and Asian) governments in the wave of urbanisation and globalization.